2005
DOI: 10.1177/014107680509800105
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Assessment Unit—Effective Strategy for Improvement of the Emergency Surgical Pathway?

Abstract: A special unit was set up in an associate teaching hospital to provide a fast-track route for the assessment of acute adult surgical and urological referrals. During an audit period of eight weeks, this surgical assessment unit had 550 referrals, of which 196 (36%) came via the accident and emergency (A&E) department; the other 354 came directly from general practitioners or other hospital departments. Mondays, Tuesdays and Fridays were the busiest days of the week; 57% of all patients arrived between 8 am and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Analysis of the overall number of patients attending SAU during both study periods revealed that the existence of the SAU resulted in the diversion of up to 2540 patients per year away from the A&E department. This figure is comparable with the 2301 patients per year reported in our earlier study (4). It would have been necessary to assess these patients in the A&E department had there not been a fully functioning SAU in our hospital.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Analysis of the overall number of patients attending SAU during both study periods revealed that the existence of the SAU resulted in the diversion of up to 2540 patients per year away from the A&E department. This figure is comparable with the 2301 patients per year reported in our earlier study (4). It would have been necessary to assess these patients in the A&E department had there not been a fully functioning SAU in our hospital.…”
Section: Discussionsupporting
confidence: 91%
“…We have previously published a detailed description of the SAU at Medway Maritime Hospital (4) which serves a population of 330,000 people. The unit, which was opened in 2003, provides a fast‐track route for adult (age 16 years and over) emergency surgical and urological referrals, allowing rapid assessment and diagnosis and where appropriate, early access to the operating theatres.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Surgical and medical admission units in other centres have been reported to reduce all cause mortality, reducing length of stay and diverting a significant number of patients from the ED. 5,6 With this in mind and to overcome the aforementioned issues the department developed the concept of a co-localized dedicated surgical assessment and review area (SARA) within their existing inpatient bed stock. In addition, dedicated medical and nursing staffs were allocated to the unit to ensure optimal patient flow.…”
Section: Introductionmentioning
confidence: 99%
“…Currently in the UK, undergraduate urological exposure is not compulsory, with fewer than half of UK medical schools offering a formal placement with a urological team . Similarly on the international platform, urology has a low priority in the curriculum of medical schools . This is particularly concerning given that urological emergencies account for more than 20 per cent of all acute surgical admissions and 5–10 per cent of general practitioner visits …”
mentioning
confidence: 99%